Environmental impact analysis of two large scale irrigation schemes in Ethiopia - Ruffeis, D.; Loiskandl, W.; Spendlingwimmer, R.; Schonerklee, M.; Awulachew, Seleshi Bekele; Boelee, Eline; Wallner, K. (2008)
This article presents the finding of a study undertaken to assess the status-quo and significant environmental impacts of two selected large-scale irrigation on natural resources in Ethiopia. Main focus is on the environmental impacts of irrigation on natural resources with special emphasis on soil quality, water quality and downstream impacts, hydrology and potential interference with ecosystems. For this purpose two schemes were selected. Wonji/Shoa Sugar Plantation is located in the Upper Awash Basin and Finchaa Valley Sugar Estate located in the Blue Nile Basin. It is well known that irrigation projects can have several adverse environmental impacts that may threaten the sustainable production of agricultural goods, which is of major importance and interest in Ethiopia since it contributes 44 percent to Ethiopia?s GDP, employs 80 percent of the labor force, and provides a livelihood to 85 percent of the nearly 80 million population (Awulachew, 2006, Government of Ethiopia, 2006, UNDP, 2006). Irrigation projects inter alia can have potential impacts on the hydrological characteristics of aquifers, quality of downstream water bodies, quality of soils and ecosystems. The most prominent results and environmental impacts of the selected case study sites could be summarized as follows. In general the irrigation water is of good quality, but the electric conductivity is unfavorable to the adjusted sodium ratio, which leads in some instances to soil crusting and has a negative impact on infiltration rate. In Wonji/Shoa the groundwater table has risen due to improper irrigation management and seepage of reservoirs. In Fincha a valuable ecosystem has been destroyed due to the establishment of the scheme and increased migration.